Stroke prevention: Evaluation of the use of anticoagulation in the population with known Atrial Fibrillation - Fatemeh Torabi; Ashley Akbari; Dan Harris; Julian Halcox; Andrew Haxton; Navjot Kalra; Ronan Lyons (International Journal of Population Data Science, 2018)
Introduction Atrial Fibrillation (AF) is a common abnormal heart rhythm that is associated with five times the risk of stroke and twice the risk of death. However, this risk can be reduced by approximately two thirds through the appropriate use of anticoagulation (AC).